Comparison of the Role of High Neutrophil to Lymphocyte Ratio with Leukocytosis in Diagnosing Acute Cholecystitis - Khalid, Muhammad Umair; Ashraf, Muhammad Ayub; Zainab, Azka; Zaka Ur Rehman; Muhammad Sufyan; Fizza Fatima (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the diagnostic accuracy of high neutrophil-to-lymphocyte ratio levels versus leukocytosis in detecting acute cholecystitis. Study Design: Cross-sectional validation study. Place and Duration of Study: Department of General Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Dec 2021 to Jun 2022. Methodology: One hundred eighteen patients with the clinical diagnosis of acute cholecystitis were included in the study. Patients with neoplastic or autoimmune disease or ongoing chronic infections were excluded. All patients underwent a test for complete blood counts to document the total leucocyte count and the neutrophil-to-lymphocyte ratio. The diagnosis of acute cholecystitis was confirmed on contrast-enhanced computed tomography abdomen. Results: The study sample had a mean age of 46.56±13.78 years, with 81(68.6%) females. The total leucocyte count had a sensitivity of 67.1%, a specificity of 73.3% and a diagnostic accuracy of 69.5% for predicting the presence of acute cholecystitis. In contrast, the neutrophil to lymphocyte ratio, with a cut-off of 3, had a sensitivity of 73.7%, a specificity of 68.9% and a diagnostic accuracy of 71.2% in predicting the presence of acute cholecystitis using contrast-enhanced computed tomography as a gold standard. Conclusion: Both total leucocyte count and the neutrophil to lymphocyte ratio were equally effective for diagnosing acute cholecystitis in clinically diagnosed patients.